Dampak Budaya Organisasi dan Kepemimpinan Asta Brata terhadap Kinerja Organisasi - Dwi Cahyanti, Ni Kadek Tika; Wilyadewi, Ida I Dewa Ayu Yayati (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Cooperatives have the aim of improving the welfare of their members through the distribution of remaining business profits. Cooperatives now face intense competition with other financial institutions, especially bank financial institutions. Improving organizational performance is a cooperative strategy so that it can survive and develop. The goal that is expected to be achieved is to determine the influence of organizational culture based on Tri Hita Karana and Asta Brata leadership on organizational performance in cooperatives in Abiansemal District, Badung Regency. The population in this study were 139 heads or managers of cooperatives in Abiansemal District. The sample size determined was 58 cooperative heads or managers using simple random sampling techniques. The analysis technique used is multiple linear regression. The results of the analysis prove that organizational culture based on Tri Hita Karana and Asta Brata leadership has a significant effect on organizational performance. Suggestions given include holding work environment cleaning activities at least once a week and leadership always following applicable regulations.